Learning Analysis of Technological Pedagogical Content Knowledge (TPACK) of Pancasila and Civic Education Teachers of State Vocational High Schools in Pekanbaru - Nurma Yunita; Supentri Supentri; Mirza Hardian (CV. Rayyan Dwi Bharata, 2023)
The background of this research is the teachers who have not fully implemented TPACK. During the implementation of TPACK in schools by teachers, many teachers are not familiar with the term TPACK, but on average they have implemented some of the indicators in TPACK. Therefore it is very necessary to examine how the teacher teaches, the use of technology when learning and others. The formulation of the problem in this study is How is Technological Pedagogical Content Knowledge (TPACK) PPKn Teachers of SMK Negeri Se-Pekanbaru. This study aims to determine the Learning Analysis of Technological Pedagogical Content Knowledge (TPACK) for PPKn Teachers at State Vocational Schools in Pekanbaru. This research is included in the quantitative research with a descriptive survey method. The population in this study were all PPKn teachers in Pekanbaru State Vocational Schools, totaling 32 people with a sample of 17 people. Based on the research results, it was found that the results of the Technological Pedagogical Content Knowledge (TPACK) Learning Analysis of PPKn Teachers at Sepekanbaru State Vocational Schools were in the